2021
DOI: 10.3389/fmicb.2021.739695
|View full text |Cite
|
Sign up to set email alerts
|

From Merkel Cell Polyomavirus Infection to Merkel Cell Carcinoma Oncogenesis

Abstract: Merkel cell polyomavirus (MCPyV) infection causes near-ubiquitous, asymptomatic infection in the skin, but occasionally leads to an aggressive skin cancer called Merkel cell carcinoma (MCC). Epidemiological evidence suggests that poorly controlled MCPyV infection may be a precursor to MCPyV-associated MCC. Clearer understanding of host responses that normally control MCPyV infection could inform prophylactic measures in at-risk groups. Similarly, the presence of MCPyV in most MCCs could imbue them with vulnera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 213 publications
(324 reference statements)
0
32
0
Order By: Relevance
“…The current ambiguity regarding MCPyV cell tropism and host range has complicated efforts to generate natural infection animal models [ 89 , 94 ]. Several groups have demonstrated that MCPyV pseudoviruses can achieve entry into a variety of human and animal cell types in vitro , including epithelial cells and fibroblasts [ 87 , 102 , 289 ].…”
Section: Preclinical Models Of Mcpyv Infection and Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…The current ambiguity regarding MCPyV cell tropism and host range has complicated efforts to generate natural infection animal models [ 89 , 94 ]. Several groups have demonstrated that MCPyV pseudoviruses can achieve entry into a variety of human and animal cell types in vitro , including epithelial cells and fibroblasts [ 87 , 102 , 289 ].…”
Section: Preclinical Models Of Mcpyv Infection and Diseasementioning
confidence: 99%
“…During viral replication of both viruses, a temporally regulated gene expression cascade yields ‘early’ and ‘late’ proteins [ 90 , 91 ]. Aside from being directly involved in viral replication, the early genes also help create a cellular environment conducive for viral replication by driving cell cycle entry [ [92] , [93] , [94] , [95] , [96] , [97] ], which is necessary for the infected host cell to support viral DNA replication and progeny virus production. When removed from the context of viral replication, many of these same functions moonlight as oncogenic properties.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this review is to provide an overview of the pro and contra evidence that argues for or against a possible role of nHPyVs in cancer. The implication of MCPyV in cancer has been extensively elaborated on in recent reviews (Chang and Moore, 2012;Becker et al, 2017;Csoboz et al, 2020;Pietropaolo et al, 2020;DeCaprio, 2021;Krump and You, 2021), so this virus will therefore only briefly be considered in this review. Although an emerging role for HPyV6 and HPyV7 in cancer was recently described in an excellent review (Klufah et al, 2021), we will include these two viruses.…”
Section: Human Polyomaviruses As Proven Causative Agents In Human Dis...mentioning
confidence: 99%
“…In MCPyV-positive MCC tumors, sequences from the early region of the viral DNA genome are clonally integrated into a host cell chromosome, leading to expression of the viral small T (ST) antigen and a truncated form of the viral large T (LT) antigen [ 5 ]. The integrated MCPyV T antigens have been implicated in transformation and tumorigenesis in both in vitro and in vivo studies (Reviewed in [ 7 , 22 , 23 ]). We previously reported that these viral early proteins, together, act as tumor promoters in the skin of K14Cre-MCPyV168 transgenic mice [ 24 ].…”
Section: Introductionmentioning
confidence: 99%